Implementasi Kebijakan Larangan Iklan Rokok Di Kota Bogor Sebagai Upaya Melindungi Generasi Muda Dari Bahaya Merokok Tahun 2023 - Gibran, Kholil; Veruswati, Meita; Fikri, Ipik Muhammad; Sari, Mega Puspa (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
According to data from The Tobacco Atlas in 2019, Indonesia has the third highest smoking population in the world after China and India, at 61.5 million smokers, or 22% of the total population in Indonesia. The prevalence of smoking among young people in Indonesia aged 10–18 years has increased from 7.2% in 2013 to 9.1% in 2018. Cigarette advertisements are promotional media that can encourage target consumers to smoke, especially adolescents. Bogor City is one of the cities that has implemented a ban on cigarette advertisements in its area. The purpose of this study is to determine the implementation of Bogor Mayor Regulation Number 3 of 2014 concerning the prohibition of cigarette product billboards in Bogor City. The theory used in this research is the George C. Edward III theory, and this type of research uses a descriptive-qualitative method. The research data sources are primary and secondary data obtained through observation, interviews (12 sources), document review, and documentation. The results showed that the implementation of the cigarette advertising ban policy in Bogor City was still not implemented optimally. This was because communication had not been carried out properly by policy implementers in carrying out this mayoral regulation. Staff resources still lack personnel in their fields. Bureaucratic appointments experience obstacles because the implementers of this policy are not directly selected by superiors but through BKSDM, and the incentives of the implementers do not come from basic salaries and allowances while working. Policy implementers are expected to further optimise the socialisation process for policy targets and immediately submit to BKSDM regarding additional personnel